To health with planning: a manual for promoting active, healthy living through community planning - Dvorak, Amy (Kansas State University, 2010)
This report examines what planners can do to increase healthy lifestyles within their communities by presenting development recommendations. In the beginning of the twentieth century the discipline of city planning was dedicated to stopping the spread of infectious diseases through improved sanitation and housing. Over the years planning separated from its origins in public health. Mobility and increased technology began to drive community development and planning, and our society created environments that devalue healthy lifestyles. A wide array of activities contribute to healthy lifestyles. Five characteristics have been shown to be the most promising in promoting health. They are regular physical activity, maintaining a healthy weight, moderate alcohol consumption, not smoking, and a prudent diet. To achieve its purpose this report will explore the prevalence of adhering to healthy lifestyle characteristics and recount a brief history of community development that has contributed to decreased healthy lifestyle adherence. Through the review of past destructive practices and current initiatives to create healthy communities, a guide to community development for healthy lifestyles is laid out. This guide will allow communities to determine their location in the process of becoming a health conscious community and give them recommendations about what they can do to promote health.
Keywords: Healthy planning; Community health; Community planning; Health Sciences, Public Health (0573); Urban and Regional Planning (0999)